Church and state in Western society : established church, cooperation, and separation - Eberle, Edward J., 1955- (Farnham, Surrey, UK ; Burlington, VT : Ashgate, 2011)
"The role of religion as a contentious and motivating force in society is examined here through the lens of the church-state dynamic in countries with three very different approaches to this crucial relationship. Focusing on the United Kingdom, where there is official recognition of one religion by the state, the United States, where law imposes a separatism between religion and the state and Germany, where there is cooperation between the church and state, this book compares these three models. It describes the components of each model, illustrates their operation and uses case law to examine what each model might learn from the other. Controversial and timely issues such as the refusal of medical treatment on religious grounds, the wearing of Islamic headscarves and ritual animal slaughter are discussed with new insight, providing a comprehensive review of varied approaches to law, government and religious freedom"--Provided by publisher.
History -- Basic constitutional text and structure -- Personal religious freedom in the United Kingdom -- Personal religious freedom in Germany -- Personal religious freedom in the United States -- Church-state relations in the United Kingdom -- Church-state relations in Germany -- Church-state realtions in the United States -- Comparative observations.
Includes bibliographical references (p. [193]) and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2022. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Church and state -- Great Britain; Church and state -- Germany; Church and state -- United States; Freedom of religion -- Great Britain; Freedom of religion -- Germany; Freedom of religion -- United States; Electronic books